The Stable Trajectory Tracking Control of a Skid-Steered Mobile Platform with Dynamic Uncertainties. (9th September 2015) - Jeon, Seungwoo; Jeong, Wootae
In order to clean the surfaces of air ducts in underground facilities, recent research has been conducted on driving the control and development of an autonomous mobile duct-cleaning platform. The duct-cleaning robots removes contaminants that are inside a duct using the friction between a rotating cleaning brush and the duct surface. For the effective removal of the contaminants and stable steering control of the autonomous mobile platform, the interaction force between the brush and the duct surface needs to be measured. However, it is not possible to achieve an accurate measurement of the contact force for the duct surface and brush, which has a nonlinear deformation characteristic. Therefore, in this study, a simple and robust controller has been proposed. This controller integrates the backstepping method with an I-PD controller for the robust platform control against irregular external forces on the cleaning brush. In addition, various trajectory tracking simulations have been conducted and the results present stable trajectory tracking of the mobile platform in air duct cleaning.